Correlation between anhedonia level and cognitive function in patients with first-episode psychosis - Chen Yingmei; Chen Minmin; Cai Yinglian; Zhou Yanling; Wu Qiuxia; Zhong Siqian; Zhang Bin; Cao Liping (Sichuan jingshen weisheng, 2021)
ObjectiveTo explore the anhedonia level and its relationship with cognitive function in patients with first-episode psychosis， and to analyze the influencing factors of cognitive function.MethodsA total of 143 first-episode psychiatric patients who met the diagnostic criteria of the Diagnostic and Statistical Manual of Mental Disorders， fifth edition （DSM-5） in the Affiliated Brain Hospital of Guangzhou Medical University from December 2016 to March 2019 were selected. Positive and Negative Syndrome Scale （PANSS） was used to evaluate the patient’s psychiatric symptoms， in which N2 （emotional withdrawal） and N4 （passive/apathetic social withdrawal） were used to assess the anhedonia level， and patients whose （N2+N4） scores beyond 4 were classified into anhedonia group， and those with （N2+N4） scores less than or equal to 4 were classified into non-anhedonia group. Hamilton Depression Scale-24 item （HAMD-24） was used to measure the depressive symptoms， and the MATRICS Consensus Cognitive Battery （MCCB） was used to detect cognitive function. Then the clinical symptoms and cognitive function of two groups were compared， and the influencing factors of cognitive function were screened by multiple linear regression analysis.ResultsThe negative symptom score， general pathological symptom score and total score of PANSS in anhedonia group were significantly higher than those of non-anhedonia group， with statistical difference （P<0.05）. The score of working memory in adolescent subgroup， the scores of information processing speed， attention/alertness and vocabulary learning in adult subgroup of anhedonia group were lower than those of non-anhedonia group， with statistical difference （P<0.05）. Multiple linear regression analysis showed that the anhedonia score and the duration of untreated psychosis were the influencing factors of working memory in adolescent subgroup （P<0.05）.ConclusionPatients with high levels of anhedonia suffer more severe mental symptoms and cognitive impairment， moreover， anhedonia is one of the influencing factors of working memory in adolescents.